Exploring Factors Affecting the Quantitative Analysis of Vitexin, Imperatorin and Gallic Acid in Tri-Kaysornmas Formulation - Limsakul, Suphatson; Roopngam, Wissuta; Voeisarn, Yanisa; Pongmanachai, Thanaporn; Chotritthirong, Yutthana; Monthakantirat, Orawan; Khamphukdee, Charinya; Chulikhit, Yaowared; Daodee, Supawadee (Indian Journal of Pharmaceutical Education and Research, 2025)
Background: The Tri-kaysornmas formula is one of the Thai traditional formulas in Thailand. Many phytochemical active compounds are found in this formula such as vitexin, imperatorin and gallic acid. Objectives: The current study explores the factors affecting the quantitative analysis of some active compounds in Tri-kaysornmas formulation. Materials and Methods: To quantify the content of these compounds, high-performance liquid chromatography was applied. A reverse-phase column, Hypersil ODS was used, and the absorbance detection was at 254 nm (imperatorin), 275 nm (gallic acid) and 340 nm (vitexin). Two factors including flow rate and acetonitrile composition in the HPLC system's mobile phase and 3 responses including capacity factor, tailing factor and number of theoretical plates were studied. Three level factorial designs with response surface methods were selected for this study. Experimental design with a 3-level flow rate from 0.8-1.2 mL/min and 3-level percentage acetonitrile from 10-15% were set. Results: For imperatorin, only capacity factor response could be explained and statistically related to and affected by the variable factors, flow rate and percentage of acetonitrile at p-value <0.0001 with the model showing significant linear effected. The model equations of gallic acid could predict all the responses (capacity factor, tailing factor and number of theoretical plates). From the ANOVA results all p-values were less than 0.05 (0.0012, <0.0001 and <0.0001 in respectively). From the ANOVA results of vitexin, the statistical analysis of RSM for capacity factor and number of theoretical plates performed a good-fitted model at a p-value less than 0.0001. Conclusion: it could be concluded that both flow rate and acetonitrile composition in the mobile phase affect the parameters including capacity factor, tailing factor and number of theoretical plates with different manner for each compound depending on the physicochemical properties. Therefore, the HPLC analysis of imperatorin, gallic acid and vitexin, the main active components in the Tri-karsornmas formula, should consider these factors to achieve high-quality separation and determination.
Keywords: Experimental design; HPLC; Response surface method; 3-level factorial design; Tri-kaysornmas formula